Specimen Writings of the Arabic and Arwi Calligraphical Works of Tamil Nadu State of India - Dr.K.M.A.Ahamed Zubair (Journal of Calligraphy, 2023)
Script is a means of communicating thoughts, ideas, and concepts. Through this medium, ideas are conveyed from one person to another, from one place to another, and from the past to the present and recorded for the future. The Arab Muslim traders and the native Tamil converts to Islam in Tamil Nadu state of India, and Sri Lanka came into closer contact as a result of their commercial activities. They were bound by a common religion, but separated by two different languages. They felt the necessity for a link language. They started to write Tamil in an adapted Arabic script called as Arwi. The Arwi script represents the Tamil language using an Arabic style of scripts. Arabic is the language of the Qur'an and Hadith. It is the medium through which the Islamic concepts and laws is conveyed to us. It is impossible to know what Allah wants us to do without knowing and understanding Arabic. Without Arabic we would deprive ourselves of the fruits of almost fourteen centuries of Islamic scholarship. Arabic and Arwi Calligraphical Scripts employed by the Muslims of Tamil Nadu State of India reflect their means of writing. These writings put many of scholarly works more productive and accessible to the public. The primary objective of this study is to share their magnificent literary history and the Islamic legacy of Arabic and Arwi Calligraphical Works and their specimen Writings in these two languages. The role of these two scripts are very influential in Islamic discourse and Islamic knowledge. This study discusses specimen Writings of Calligraphic nature in palm leaves, unpublished books, printed books, letters, manuscript collections, inscription stones, tombstones with or without chronograms, documents and etc., It is an analytical cum descriptive study of these Calligraphical Works in Arabic and Arwi. The primary objective of this study is to share the impact of Arabic and Arwi Calligraphical Script on Muslims of Tamil Nadu and their magnificent literary history and the Islamic life.النص هو وسيلة لتوصيل الأفكار والأفكار والمفاهيم. من خلال هذه الوسيلة ، يتم نقل الأفكار من شخص إلى آخر ، ومن مكان إلى آخر ، ومن الماضي إلى الحاضر وتسجيلها للمستقبل. أصبح التجار العرب المسلمون والتاميل الأصليون الذين اعتنقوا الإسلام في ولاية تاميل نادو الهندية ، وسريلانكا على اتصال وثيق نتيجة لأنشطتهم التجارية. كانوا مرتبطين بدين مشترك ، لكن مفصولين بلغتين مختلفتين. شعروا بضرورة وجود لغة ارتباط. بدأوا في كتابة التاميل بخط عربي معدّل يسمى Arwi. يمثل خط العروي لغة التاميل باستخدام أسلوب الكتابة العربية. اللغة العربية هي لغة القرآن والحديث. إنها الوسيلة التي يتم من خلالها نقل المفاهيم والقوانين الإسلامية إلينا. من المستحيل معرفة ما يريدنا الله أن نفعله دون معرفة اللغة العربية وفهمها. بدون اللغة العربية لحرمنا أنفسنا من ثمار ما يقرب من أربعة عشر قرنا من الدراسات الإسلامية. تعكس الخطوط العربية والخطوط العروية التي يستخدمها مسلمو ولاية تاميل نادو الهندية وسائلهم في الكتابة. جعلت هذه الكتابات العديد من الأعمال العلمية أكثر إنتاجية ومتاحة للجمهور. الهدف الأساسي من هذه الدراسة هو مشاركة تاريخهم الأدبي الرائع والإرث الإسلامي من الأعمال العربية وخط العروي وكتاباتهم النموذجية بهاتين اللغتين. دور هذين الخطين مؤثر للغاية في الخطاب الإسلامي والمعرفة الإسلامية. تناقش هذه الدراسة نماذج من كتابات الطبيعة الخطية في سعف النخيل ، والكتب غير المنشورة ، والكتب المطبوعة ، والحروف ، ومجموعات المخطوطات ، وأحجار النقوش ، وشواهد القبور مع أو بدون كرونوغرامات ، ووثائق ، وما إلى ذلك ، وهي دراسة تحليلية وصفية لهذه الأعمال الخطية باللغة العربية. وعروي. الهدف الأساسي من هذه الدراسة هو مشاركة تأثير الخط العربي والخط العربي على مسلمي تاميل نادو وتاريخهم الأدبي الرائع والحياة الإسلامية.